1991
DOI: 10.1159/000147134
|View full text |Cite
|
Sign up to set email alerts
|

Configurational and Volumetric Changes of the Early Prenatal Human Cerebellar Dentate Nucleus

Abstract: The three-dimensional configurational and volumetric changes of the human dentate nucleus (DN) during intrauterine life were examined in 11 fetuses (11 to 27–28 weeks of gestation). During intrauterine life, the dentate nuclear profile successively passes through the pongid, cercopithecus and prosimian phases of configuration. The smooth, elongated, crescent-shaped DN of 11 weeks lies along a dorsal-ventral axis. A 45 ° clockwise shift in the position of the nucleus changes the axis to dorsomedial-ventrolatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…At 34 weeks, the cells of the DM region had a greater density of spines than those in the VL 193 region. This corroborates our earlier findings in Nisslstained sections [13], where wc observed that not only do convolutions begin to appear first in the DM region, but also that cells in this region mature earlier than those in the VL region.…”
Section: Discussionsupporting
confidence: 92%
“…At 34 weeks, the cells of the DM region had a greater density of spines than those in the VL 193 region. This corroborates our earlier findings in Nisslstained sections [13], where wc observed that not only do convolutions begin to appear first in the DM region, but also that cells in this region mature earlier than those in the VL region.…”
Section: Discussionsupporting
confidence: 92%
“…Primary gyri (arrow) and a short fissure (arrowhead) are observed. In humans, the DN can be recognized in the destined site of cerebellar white matter as early as 11-12 WG (Hayaran et al 1991;K. Yamaguchi, N. Goto, unpublished observations).…”
Section: Discussionmentioning
confidence: 91%
“…According to her results, only a short fissure running rostrocausally is formed in the smooth lateral surface even in adult monkeys. Few attempts, on the other hand, have been made for 3D reconstruction analyses in humans, to our knowledge (Owaki 1958;Hayaran et al 1991). Therefore, we have applied a computerized reconstruction technique, a kind of shaded surface rendering, to explore the exact 3D structure and its developmental changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations